2019
DOI: 10.5194/tc-13-2075-2019
|View full text |Cite
|
Sign up to set email alerts
|

Airborne radionuclides and heavy metals in high Arctic terrestrial environment as the indicators of sources and transfers of contamination

Abstract: Abstract. A survey of airborne radioactive isotopes (137Cs, 238Pu, 239+240Pu, 241Am, and 210Pb) and trace metals (Pb, Cu, Zn, Cd, Fe, Al) in tundra soils and cryoconite hole material sampled from several locations in the Kaffiøyra region of Spitsbergen revealed significant variability in spatial concentration. Lithogenic radionuclides (230Th, 232Th, 234U, 238U) show less variability than the airborne radionuclides because their activity concentrations are controlled by mixing of local material derived from dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Our results show that elemental carbon is accumulated in cryoconite with respect to Alpine snow, where typical concentrations are orders of magnitude lower (Jenk et al, 2006). Only contaminated urban soils present an elemental carbon concentration comparable to Alpine cryoconite samples (Lorenz et al, 2006). These findings support the hypotheses by Hodson (2014), who has suggested that cryoconite plays a role in extending the residence time of black and elemental carbon on the surface of glaciers, with implications for the accumulation of hydrophobic contaminants and for ice darkening.…”
Section: Carbonaceous Contentsupporting
confidence: 81%
“…Our results show that elemental carbon is accumulated in cryoconite with respect to Alpine snow, where typical concentrations are orders of magnitude lower (Jenk et al, 2006). Only contaminated urban soils present an elemental carbon concentration comparable to Alpine cryoconite samples (Lorenz et al, 2006). These findings support the hypotheses by Hodson (2014), who has suggested that cryoconite plays a role in extending the residence time of black and elemental carbon on the surface of glaciers, with implications for the accumulation of hydrophobic contaminants and for ice darkening.…”
Section: Carbonaceous Contentsupporting
confidence: 81%
“…Cryoconite is a promising environmental matrix to study the radioecology of the Arctic and other glacial regions 1 , 2 . Sediments in the bottoms of cryoconite holes usually consist of dark, often black granules, which are minerals (80–98 mass%) and organic matter (2–20 mass%) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Cryoconite absorbs solar radiation, and associated melting leads to the formation of cylindrical holes in the glacier surface. The ability of cryoconite to accumulate natural and anthropogenic radionuclides from the atmosphere to very high activity levels has been shown in a number of publications 1 , 2 , 4 – 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meltwater is in fact the means by which the impurities deposited in the past on the glacier, and subsequently preserved in snow and ice layers, come into contact with cryoconite (Baccolo, et al, 2019). Studies have shown that cryoconite accumulates both natural FRN, such as 210 Pb and 7 Be, and anthropogenic FRN, such as 137 Cs, Pu and Am isotopes, which were released in the environment as a consequence of nuclear accidents, test explosions and atmospheric re-entries of nuclear powered satellites (Tieber, et al, 2009;Baccolo, et al, 2019;Łokas, et al, 2019). After being accumulated at the surface of glaciers, cryoconite and its radioactive content are released by glaciers in association with meltwater.…”
Section: Introductionmentioning
confidence: 99%